Dynamic Location Modelling in 3D Beamforming for 5G Mobile Communications - Sasi A; Santhiya P (Computer Engineering and Applications Journal, 2015)
Mobile communication system is designed to provide reliable communication with more number of services and with low cost among multiple users. Due to limited frequency spectrum and resources, mobile communication requires more development in case of both establishing communication and maintenance in service quality. To fulfill these requirements, 5G mobile communication is being developed to provide high quality reliable communication and quality of service, by using beamforming model. As the trend of next generation mobile communication, 3D directional transmission is considered to give enhanced coverage model and reusability of frequency. Phase arrayed antenna is used in this beamforming model to give orthogonal communication among users. In this paper, a new modeling of beamforming is applied to give a new dimension by considering altitude with potential field strategy. Here phase arrayed antenna is replaced by 3-D smart antenna to improve the performance of 5G mobile communications. Performance evaluation outcomes 3D beamforming leads 2D beamforming in terms of communication delay, and uplink downlink throughput.